The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

How to estimate age of old bottlenose dolphins (Tursiops truncatus); by tooth or pectoral flipper? - Ashley Barratclough; Wayne E. McFee; Megan Stolen; Aleta A. Hohn; Gretchen N. Lovewell; Forrest M. Gomez; Cynthia R. Smith; Daniel Garcia-Parraga; Randall S. Wells; Celeste Parry; Risa Daniels; Sam H. Ridgway; et al. (Frontiers in Marine Science, 2023)
Multiple techniques have been used for estimating age in bottlenose dolphins ( Tursiops truncatus ). The longest established technique is via counts of growth later groups (GLGs) in the longitudinal section of an extracted mandibular tooth. Previous studies to validate GLGs have primarily used younger dolphins (less than 16yrs old) due to the limited number of known age older animals. This study assessed the accuracy of age estimates for bottlenose dolphins using both GLG analysis and a newer technique, pectoral flipper radiography (PFR) for dolphins ranging from 0 to 58yrs, with a majority of samples (70%) over 16yrs. GLGs were assessed by two expert independent readers on tooth sections from 52 different dolphins (85% over 16yrs, maximum age 58yrs), and assessments of PFRs were performed by two experienced veterinarians on 37 dolphins (54% over 16yrs, maximum age 54yrs). Results demonstrated both techniques became less accurate in older dolphins, particularly those > 30yrs, with errors as large as 37yrs for GLG estimates. The root mean squared error (RMSE) for age estimation using GLGs for dolphins ≤15 years of age was 1.46yrs compared to 1.58yrs using PFRs demonstrating the accuracy of both techniques in this age bracket. For dolphins >30yrs, RMSE increased to 17yrs in GLG aging and 8.25yrs in PFR. Challenges in obtaining accurate age estimates in GLGs were primarily due to sectioning and staining difficulties in visualizing the newest GLG layers, in the very old animals. Complications in reading the layers included obtaining a good section, the presence of accessory layers, GLG compression, and tooth curvature or wear removing the neonatal line influencing aging biases. In pectoral flipper aging, the primary challenge was obtaining a true dorsoventral radiograph in a live dolphin during a health assessment, as well as the subjective assessment of scoring and reliance on degenerative changes accurately estimate age in geriatric dolphins. While access to the radiography equipment can be a limiting factor, the improved accuracy for age estimation in adult dolphins, the less invasive nature, and reduced processing time to results make pectoral radiography a preferred alternative technique for estimating age in live dolphins.

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Candidate gene database and transcript map for peach, a model species for fruit trees - Renate Horn; Anne-Claire Lecouls; Ann Callahan; Abhaya Dandekar; Lilibeth Garay; Per McCord; Werner Howad; Helen Chan; Ignazio Verde; Doreen Main; Sook Jung; Laura Georgi; et al. (Theoretical and Applied Genetics, 2005)